ANALISIS INTEGRASI PASAR HARGA AYAM BROILER DI PROVINSI JAWA TIMUR - Subagja, Hariadi; Hartono, Slamet; Santosa, Krisnha Agung; Jamhari, Jamhari (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2011)
This research is aimed to measure integration rate of broiler price and the relation of broiler price among the regions in East Java Province. This research was conducted from 2000 up to 2009 by survey approach. The secondary data of monthly broiler price at consumer level in Jombang, Malang, Jember and Surabaya regencies published by agriculture and animal husbandry departments as well as East Java statistical bureau were used. The descriptive and market integration analysis of co-integration Johansen and Granger causality test were used. The research showed that broiler markets in East Java were integrated and efficient. The analysis of Granger causality in the four regencies in East Java showed that the two-way causality of broiler price was pointed in Jombang-Malang, Jombang-Surabaya, Surabaya-Jember regencies respectively. Meanwhile the one-way causality was pointed in Jombang-Jember, Malang-Jember, Surabaya-Jember, and Surabaya-Malang.